2017
DOI: 10.1016/j.jacc.2016.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus–Induced Microvascular Destabilization in the Myocardium

Abstract: Diabetes mellitus destabilized microvascular vessels of the heart, affecting the amplitude of therapeutic neovascularization via rAAV.Tβ4 in a translational large animal model of hibernating myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 34 publications
4
117
0
1
Order By: Relevance
“…Mechanisms of this type that have been implicated in the development of retinopathy include inflammation, oxidative stress and persistent activation of the renin–angiotensin system . In addition, microvascular disease may particularly affect the myocardium in patients with diabetes which is clearly of greatest danger in patients with already dysfunctional myocardium . Due to the suggestion of less benefit of drug therapy and higher rates of diabetic complications in African‐Americans, we repeated analyses without these patients with similar results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of this type that have been implicated in the development of retinopathy include inflammation, oxidative stress and persistent activation of the renin–angiotensin system . In addition, microvascular disease may particularly affect the myocardium in patients with diabetes which is clearly of greatest danger in patients with already dysfunctional myocardium . Due to the suggestion of less benefit of drug therapy and higher rates of diabetic complications in African‐Americans, we repeated analyses without these patients with similar results .…”
Section: Discussionmentioning
confidence: 99%
“…11 In addition, microvascular disease may particularly affect the myocardium in patients with diabetes which is clearly of greatest danger in patients with already dysfunctional myocardium. 19 Due to the suggestion of less benefit of drug therapy and higher rates of diabetic complications in African-Americans, we repeated analyses without these patients with similar results. 20,21 Another potential risk factor for developing heart failure in diabetes patients with microvascular complications is their presumed more severe diabetes and for this reason intensified glucose-lowering therapy, where some drug classes including pioglitazones have been linked to an increased risk of heart failure.…”
Section: Risk According To Type Of Microvascular Complicationmentioning
confidence: 99%
“…For several tissues, there is already evidence for morphological or functional alterations. A recent study of myocardium showed capillary rarefaction and reduced pericyte investment in 5-month-old MIDY pigs compared to age-matched WT littermates [27]. Additionally, the retina of MIDY pigs (age: 24 or 40 months) exhibited several diabetes associated morphologic alterations [28].…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular insufficiency takes a critical role in the development of DCM. Accumulating evidences have demonstrated a progressive reduction of the microvasculature and an impaired angiogenic response to chronic ischemia with the development of diabetes [2, 3]. These microvascular changes may lead to reduced perfusion of myocardium and contribute to adverse cardiovascular events [4].…”
Section: Introductionmentioning
confidence: 99%